Kebijakan Pemerintah Dalam Mengatasi Pencemaran Limbah Industri Penyamakan Kulit (Studi pada Badan Lingkungan Hidup dan Dinas Perindustrian & Perdagangan Kabupaten Magetan) - Rosseto, Wibby Roza (Jurnal Administrasi Publik, 2013)
Abstract: The Government Policy in Dealing With The Waste Pollution of Leather Tanning Industry. The background of research is the problem of waste pollution of leather tanning industry. The community shall aware of the negative impact of this problem because if it remains unsolved, it may influence the profitability of leather industry in Magetan. Research type is descriptive with qualitative approach. The focus of this problem (1) The complexity of waste pollution of leather tanning industry in Magetan District (2) The response against waste pollution of lather tanning industry in Magetan District (3) The recommended policy to deal with waste pollution of lather tanning industry in Magetan District. Result of research indicates that Magetan District has, indeed, witnessed the experience of waste pollution of leather tanning industry. There is a high degree of complaint from the community against this waste pollution. The role of stakeholders in responding the problem of waste pollution from leather tanning industry in Magetan District is less than optimum.Keywords: Policy, Pollution, Waste, Leather IndustryAbstrak: Kebijakan Pemerintah Dalam Mengatasi Pencemaran Limbah Industri Penyamakan Kulit. Penelitian ini dilakukan karena terdapat permasalahan pencemaran limbah industri kulit di Kabupaten Magetan. Hal tersebut juga akan membawa dampak negatif untuk kedepannya bagi industri kulit di Magetan jika masalah limbah tersebut tidak segera di atasi. Penelitian ini bersifat deskriptif dengan pendekatan kualitatif. Fokus permasalahannya adalah (1) Kompleksitas permasalahan pencemaran limbah industri penyamakan kulit di Kabupaten Magetan (2) Tanggapan para stakeholders terhadap pencemaran limbah industri penyamakan kulit di Kabupaten Magetan (3) Rekomendasi kebijakan dalam mengatasi pencemaran limbah industri penyamakan kulit di Kabupaten Magetan. Hasil penelitian menunjukkan, bahwa Kabupaten Magetan mengalami permasalahan pencemaran limbah industri kulit. Hal tersebut dapat dilihat dari respon masyarakat yang banyak mengeluhkan tentang limbah tersebut. Selain itu, peran stakeholders dalam merespon permasalahan pencemaran limbah industri kulit di Kabupaten Magetan masih belum optimal.Kata kunci: Kebijakan, Pencemaran, Limbah, Industri Kulit